Oral Hygiene Education and Tobacco Cessation Counseling for Patients Attending in the Dental Outpatient Department of a Selected Private Dental College (Journal of Dentistry and Allied Science, 2025)
Aim: The study aimed to assess the sociodemographic characteristics, systemic diseases, consumption of tobacco products and oral hygiene practices among patients attending in the dental outpatient department (OPD) of the University Dental College and Hospital (UDC&H), followed by oral hygiene education, demonstration, and tobacco cessation counselling (TCC). Methods: A convenience sampling method was used to recruit 478 patient who attended in the dental OPD of UDC& H from February 2024 to August 2024. Permission and informed consent were taken from hospital director of UDC&H and patients respectively. The study was done in two phases. Firstly, a descriptive cross-sectional study was undertaken employing a pretested, standardized, semi-structured interview administered questionnaire through Google Forms to acquire information regarding sociodemographic characteristics, oral hygiene practices, systemic diseases and consumption of tobacco products. After that, in second phase, based on the findings, relevant oral hygiene education (instruction and demonstration) and TCC were offered and documented. Data obtained from Google Forms, were converted to a Microsoft Excel spreadsheet and later analyzed using IBM Statistical Package for Social Sciences (SPSS) Version 27 and statistics, including frequency, percentage, mean ±standard deviation, were presented in both tabular and figure formats. Results: Majority of the participants in our study were male 244 (51.0%). The mean age was 33.97±16.38 years, with young adults aged 18-32 years (34.7%), followed by 33-47 (25.7%). Most of them were married (69.0%) and had finished graduation (31.4%). The largest category participants were housewives (31.2%), followed by students (28.2%). Most reported (80.3%) no systemic health difficulties, and just 7.2% used any form of tobacco products. Dental hygiene practices vary, with only 44.1% tooth brushing twice daily and 33.4% brushing after breakfast. A mere 2.3% did interdental cleaning regularly, only 5.0% consistently rinsed after-meal, and only 5.2% did tongue clean regularly. Oral hygiene instruction, tooth brushing, and dental flossing demonstrations were employed for all the participants, whereas TCC was given only 7.2% participants. Conclusion: The study highlights the need for comprehensive oral health education, addressing systemic diseases and oral hygiene practices, and tobacco cessation counseling. It suggests prioritizing research and oral health educational programs to improve adherence to recommended practices in dental OPD during intern rotation.Journal of Dentistry and Allied Science, Vol. 7 No 2: 53-64